Lesson study in mathematics initial teacher education in England - Fay Baldry; Colin Foster (2019)
Drawing on research in mathematics initial teacher education (ITE) in England, this chapter explores the potential of lesson study to support pre-service mathematics teachers’ pedagogical development. We draw attention to ways in which lesson study can be highly transformative of beginning mathematics teachers’ pedagogical learning. We consider the current ITE context in England and analyse potential opportunities and challenges for incorporating lesson study into mathematics ITE courses. We conclude by proposing a theoretical model for using lesson study in mathematics ITE that takes account of these contextual issues and offers ways to make the most of the opportunities available. We particularly highlight the importance of a productive partnership between university and school, the need to focus both collaborative lesson planning and observation on a clear research question that relates to student learning of mathematics, and the necessity of a tight protocol for post-lesson discussions.